Sugarcane bagasse delignification with potassium hydroxide for enhanced enzymatic hydrolysis - Paixão Alves, Susana (2016)
The optimization of an alkaline pretreatment process for the delignification of sugarcane bagasse (SCB) to enhance the subsequent enzymatic hydrolysis was performed according to the Doehlert uniform shell design. In this experimental design, the effect of two factors—potassium hydroxide (KOH) concentration and autoclaving time at 121 C (1 atm)—on cellulose, hemicellulose, or the total polysaccharide and lignin content in SCB was evaluated. This response surface methodology revealed that KOH concentration is the factor that most influences the chemical characteristics of treated SCB (SCBt), with optimal conditions for the highest delignification being KOH in the range 5–10% (w/v) and an autoclaving time of 35 min, which provides an average of 97% total polysaccharides without inhibitor accumulation (furfural, 5-hydroxymethyl furfural) and #5% lignin. SCBt samples from two pretreatment conditions (KOH 3.25% – 13 min; KOH 10% – 35 min) were selected, based on the greatest delignification (70–74%) and polysaccharide availability (95–97%) after pretreatment, and further hydrolysed for fermentable sugar production. High sugar yields were obtained from both the pretreated samples (866 to 880 mg sugar per g biomass, respectively) in contrast with the 129 mg sugar per g raw biomass obtained from untreated SCB. These results demonstrate the effectiveness of KOH alkali pretreatments, which improves the overall digestibility of raw SCB polysaccharides from about 18% up to 91%. However, harsh alkali treatment (KOH 10%) is the most effective if the highest glucose/xylose ratio in the final sugar-rich hydrolysate is the aim. Hence, the use of sugar-rich hydrolysates obtained from SCBt as the carbon source for industrial purposes may provide a sustainable and economic solution for the production of bio-based added-value products, such as second generation (2G) bioethanol.